Key terms in stylistics - Nørgaard, Nina; Montoro, Rocío; Busse, Beatrix (Continuum, 2010)
Introduction -- Key branches in stylistics -- Key terms in stylistics -- Key thinkers in stylistics -- Key texts in stylistics
Includes index
Keywords: Wörterbuch; Stilistik